Politik Pangan: Konstruksi Kebijakan Dalam Rangka Konsolidasi Ketahanan Ekonomi Indonesia (Tinjauan Sosio-Historis Kultural Ekonomi Islam) - Arin Setiyowati (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2018)
ABSTRACT Ghazan Khan (1295-1353 M) and Sultan alauddin Khidji (1296-1316 M), both of them are Islamic leader who succes in Persia and india. They can drive their state Islamic system throught equality distribution of wealth policy. Both of them have a similar power to change their not good economic system to excelent. Agricultural policy by Ghazan Khan and The price control system by Sultan Alauddin Khan. Therefore, they drive the welfare society. Indonesia, is agrarian country and economics condition still haven’t stable yet, especially it shows from some crisis tragedies both food and economy in Indonesian history. Therefore, this literature study to be effort to give a problem solving for indonesian economics condition based historical perspective from the best leader from Mongol generation. Its according with Indonesians wisdom and be urgent agenda to reformula, because food distribution sector and political will of government is important factor in food political of a state. Keywords: Ghazan Khan, Sultan Alauddin Khidji, Food and market policy, Souvereignty of Indonesians Economic.